Persons chronically exposed to low doses of ionizing radiation: A cytogenetic dosimetry study - Cherednichenko, Oksana; Pilyugina, Anastassiya; Nuraliev, Serikbai; Azizbekova, Dinara (Mutation research. Genetic toxicology and environmental mutagenesis, 2024)
The dosimetry and control of exposure for individuals chronically exposed to ionizing radiation are important and complex issues. Assessment may be optimized by evaluating individual adaptation and radiosensitivity, but it is not possible for a single model to account for all relevant parameters. Our goal was to develop approaches for the calculation of doses for persons chronically exposed to ionizing radiation, taking their radiosensitivities into consideration. On the basis of ex vivo radiation of blood samples, dose-effect models were constructed for dose ranges 0.01–2.0 and 0.01–0.4 Gy, using different cytogenetic criteria. The frequencies of "dicentric chromosomes and rings" at low doses are too low to have predictive value. The different responses of subjects to radiation made it possible to categorize them according to their radiosensitivities and to generate separate dose-effect curves for radiosensitive, average, and radioresistant individuals, reducing the amount of error in retrospective dosimetry. •Chronic low-dose exposure is an adaptive factor to the response to ionizing radiation.•Modified dose-response curves may be appropriate for chronically exposed persons, including the assessment of individual radiosensitivity.•Low dose estimates will be more accurate when models for the 0.01-0.4 Gy range are used.